Pengaruh Preparasi Sampel, Lama Ekstraksi, dan Presipitan Terhadap Karakteristik Karaginan yang Diekstraksi dari Kappaphycus alvarezii - Horisanto, Abraham; Metusalach, Metusalach; Zainuddin, Elmi Nurhaidah; Wijayanti, Willy; Pamungkas, Ilham Wahyu; Agustin, Venny; Jannah, Syerina Raihatul (Torani Journal of Fisheries and Marine Science, 2025)
Carrageenan is a polysaccharide compound product produced from carrageenophyte seaweed extraction, one of which is Kappaphycus alvarezii. The yield and other characteristics are conventionally produced from an extraction process and have different results. This study aims to explore and optimize the characteristics of carrageenan produced by treating sample preparation with two types of precipitants at specific concentrations, setting the timing during the extraction process, and examining the interaction of these three treatments on the carrageenan characteristics. The results obtained showed that the yield value, acid-insoluble ash (AIA) content, and viscosity were influenced by the preparation method, specifically by chopping the seaweed before extraction. Additionally, the characteristics of the gel strength were influenced by the preparation method, specifically by blending the seaweed. The use of KCl precipitant affects the water content, AIA content, and viscosity, while the CaCl₂ precipitant affects the yield value and gel strength. 1-hour extraction process affected the characteristics of carrageenan for AIA content and gel strength, while extraction for 2 hours affected the yield value, water content, and viscosity. The interaction of 8% KOH solvent by cutting sample treatment, extracted for 2 hours and using KCl precipitant, produced good carrageenan characteristics for water content, AIA content, and viscosity.